2010
DOI: 10.1111/j.1553-2712.2010.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of Propofol Versus Ketamine for Procedural Sedation in the Emergency Department

Abstract: Objectives: The objective was to compare the occurrence of respiratory depression, adverse events, and recovery duration of propofol versus ketamine for use in procedural sedation in the emergency department (ED).Methods: This was a randomized nonblinded prospective clinical trial of adult patients undergoing procedural sedation for painful procedures in the ED. Patients with pain before the procedure were treated with intravenous (IV) morphine sulfate until their pain was adequately treated at least 20 minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 36 publications
1
76
0
2
Order By: Relevance
“…However, because of its adverse psychological effects and the availability of other induction agents, its use diminished rapidly. Emergence reactions in children are less intense, so it can be used for both sedation and general anaesthesia in procedures such as cardiac catheterization (with caution in patients with raised pulmonary vascular resistance) 12 higher rate of subclinical respiratory depression in patients in the ketamine group than the propofol group 18 . There was no difference in the rate of clinical interventions related to respiratory depression, pain, or recall of the procedure between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of its adverse psychological effects and the availability of other induction agents, its use diminished rapidly. Emergence reactions in children are less intense, so it can be used for both sedation and general anaesthesia in procedures such as cardiac catheterization (with caution in patients with raised pulmonary vascular resistance) 12 higher rate of subclinical respiratory depression in patients in the ketamine group than the propofol group 18 . There was no difference in the rate of clinical interventions related to respiratory depression, pain, or recall of the procedure between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a retrospective case analysis suggested that sedation with the combination of ketamine and propofol can be safely performed in the pediatric ED by a skilled emergency physician [54] . The use of ketamine, 1.0 mg/kg iv followed by 0.5 mg/kg every 3 min as needed, was safe and effective for procedural sedation [55] . Additionally, propofol in conjunction with 0.5 mg/kg ketamine, compared with propofol alone, may result in less hemodynamic depression, which may be advantageous in patients with unstable hemodynamics in the ED [56] .…”
Section: Use Outside the Operating Roommentioning
confidence: 92%
“…Our primary outcome was the relative number and proportion of subjects experiencing airway or respiratory adverse events leading to an intervention, defined as the composite of 1 or more predefined airway or respiratory events and 1 or more associated predefined clinical interventions [5][6][7]36,37 (Figure 1). Research assistants continuously assessed for evidence of either one, recording monitoring values and asking treating physicians to clarify if there was any doubt.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The dissociative agent ketamine maintains cardiopulmonary stability [8][9][10] but can result in extended recovery, emesis, hypersalivation, and hallucinations. 6,8,[10][11][12][13] The popular combination of propofol and ketamine ("ketofol") is purported to reduce respiratory depression, emesis, and recovery time by counteracting the negative effects of one drug with the positive effects of the other, 11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] although the best evidence thus far does not indicate a reduction in airway and respiratory adverse events relative to propofol alone. 16,32 Ketofol has been described in 1:1 and 4:1 propofol:ketamine mixtures 14,33 ; however, the optimal formulation is not known.…”
Section: Introduction Backgroundmentioning
confidence: 99%